Life history strategy and romantic satisfaction in patients’ behavior - Ene, Cristina; Burtaverde, Vlad; Jonason, Peter Karl; Brehar, Felix; Pruna, Viorel (Frontiers in Psychology, 2024)
According to evolutionary psychologists, an individual-consciously or not-that allocates resources for somatic effort focuses on homeostasis and the protection of themselves and others. In health crisis situations, patients must choose between mobilizing their remaining resources to recover or resigning themselves to the disease. When patients choose to be proactive in terms of protecting their health, are conscientious, and compliant in the recovery process, a high level of patient activation is achieved. Therefore, we examined (N = 252) if the patients' K strategies are predictors for engagement in patient activation type behavior.Additionally, we tested the mediating effect of pain catastrophizing and the moderating effect of romantic satisfaction. We found that people with a medical diagnosis, who were in a romantic relationship, and had high-K fitness were much more likely to be activated patients.Moreover, pain catastrophizing mediated the relationship between high-K fitness strategy and patient activation, while romantic satisfaction moderated this relationship, amplifying its intensity. The findings underscore the importance of identifying patients' psychological resources (e.g., high-K strategy, romantic satisfaction, or pain perception) to keep them engaged in the health recovery process.